Institutional Micro Credit Determinants and Portfolio Quality of Investment Groups - Kalui, Fredrick M. (European Scientific Journal, ESJ, 2020)
Micro-credit plays a major role in development strategies. This is in view of its direct relationship to both poverty alleviation and improvement of the living standards. However, commercial banks are still largely absent in the provision of micro credit. This phenomenon may be attributed to credit policies associated with loans provided by the formal sector. Since many businesses in small and micro enterprise sector are largely poor and lack tangible assets that can be pledged as collateral in conventional lending, banks are unwilling to provide credit facilities to them. For this reason, The objectives of the study were to determine the effects of macroeconomic, group leverage, group capitalization and group characteristics on the portfolio quality of investment groups financed by the Sidian bank in Nairobi region The study adopted a descriptive survey research design since it establishes the relationship between the dependent and the independent variable. With the target population being all the 56 investment groups in the 9 branches under the Sidian bank within Nairobi region. The study used secondary data, which was obtained from the Sidian bank offices in each of the branches within Nairobi region. Data analysis was conducted using descriptive statistics including percentages, frequencies, means and standard deviation. In addition, inferential analysis was carried out using correlation analysis and multiple regression analysis. The study found that macroeconomic variables, group leverage level, group capitalization and group characteristics influences portfolio quality of investment groups financed by the Sidian bank in Kenya positively and significantly. The study concluded that group leverage level had the greatest influence on portfolio quality of investment groups financed by Sidian bank in Kenya followed by macroeconomic variables, group capitalization level and finally group characteristics had the least effect. The study recommends that the Sidian bank need to manage their portfolios, by understanding that not only the risk posed by each credit but also howthe risks of individual loans and portfolios are interrelated. The study also recommended that, banks should be allowed to invest more in loans and advances as long as such banks have enough reserves to finance such investments. The study further recommends that regulatory authority (CBK) and other stake holders should create an enabling environment that removes all these inefficiencies to the policy concern of high cost of credit.